2012
DOI: 10.1107/s1600536812020764
|View full text |Cite
|
Sign up to set email alerts
|

Cinnarizinium picrate

Abstract: In the title salt {systematic name: 4-diphenylmethyl-1-[(E)-3-phenylprop-2-en-1-yl]piperazin-1-ium 2,4,6-trinitrophenolate), C26H29N2+·C6H2N3O7−, the cinnarizinium cation is protonated at the piperazine N atom connected to the styrenylmethyl group; the piperazine ring adopts a distorted chair conformaiton. In the crystal, bifurcated N—H...(O,O) hydrogen bonds link the components into two-ion aggregates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…1-Benzylpiperazine was originally synthesized as a potential antihelminthic (Campbell et al, 1973) and these derivatives were found to possess excellent pharmacological activities such as vasodilator, hypotensive, antiviral activity and cerebral blood flow increasing actions, broad pharmacological action on central nerves system (CNS), especially on dopaminergic neurotransmission. In the course of our studies on the salts of piperazines (Jasinski et al, 2011;Song et al, 2012) and in view of the importance of piperazines, the paper reports the crystal and molecular structure of the title salt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Benzylpiperazine was originally synthesized as a potential antihelminthic (Campbell et al, 1973) and these derivatives were found to possess excellent pharmacological activities such as vasodilator, hypotensive, antiviral activity and cerebral blood flow increasing actions, broad pharmacological action on central nerves system (CNS), especially on dopaminergic neurotransmission. In the course of our studies on the salts of piperazines (Jasinski et al, 2011;Song et al, 2012) and in view of the importance of piperazines, the paper reports the crystal and molecular structure of the title salt.…”
Section: Methodsmentioning
confidence: 99%
“…For the biological activity of piperazine derivatives, see: Dinsmore et al (2002); Berkheij et al (2005); Humle & Cherrier (1999); Campbell et al (1973). For related structures, see: Jasinski et al (2011); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For cinnarizine in allergic disorders, see: Barrett & Zolov (1960). For related structures, see: Bertolasi et al (1980); Dayananda et al (2012); Jasinski et al (2011); Mouillé et al (1975); Smith et al (2001); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For cinnarizine as a calcium channel blocker, see: Terland & Flatmark (1999), as a nootropic drug, see: Towse (1980) and for a clinical evaluation in various allergic disorders, see: Barrett & Zolov (1960). For related structures, see: Bertolasi et al (1980); Dayananda et al (2012); Jasinski et al (2011); Mouillé et al (1975); Siddegowda et al (2011); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…Cinnarizine can be used in scuba divers without an increased risk of central nervous system oxygen toxicity. The crystal structures of some related compounds viz., cinnarizine (Mouillé et al, 1975), cyclizine hydrochloride (Bertolasi et al, 1980), cinnarizinium dipicrate (Jasinski et al, 2011), cinnarizinium picrate (Song et al, 2012), opipramolium fumarate (Siddegowda et al, 2011) and cinnarizinium 3,5-dinitrosalicylate (Dayananda et al, 2012) have been reported. In continuation of our work on the salts of pharmaceutical compounds and in view of the importance of cinnarizine, this paper reports the crystal structure of the title salt, C 26 H 29 N 2 + .…”
Section: S1 Commentmentioning
confidence: 99%